Hubungan kepemimpinan dan fasilitas K3 dengan persepsi risiko siswa dan guru pada era pasca pandemi - Nur Aini; Riscky Fitri Wahyuni (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
Occupational health and safety (OHS) in the education sector has become an important issue, particularly in the post-pandemic era characterized by behavioral changes and the emergence of safety fatigue. Risk perception, as a psychological factor, plays a crucial role in shaping safety behavior among students and teachers. This study aims to analyze the relationship between principal leadership and OHS facilities with the risk perception of students and teachers in the post-pandemic context. This research employed a quantitative analytic approach with a cross-sectional design involving 130 respondents consisting of students and teachers, selected through probability sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that principal leadership and OHS facilities are positively and significantly associated with risk perception (p < 0.05). Descriptively, both independent variables were categorized as moderate, while risk perception was at a medium level. These findings suggest that strengthening safety culture in schools requires an integrated approach involving leadership, facility support, and behavioral strategies. Therefore, optimizing leadership roles and the sustainable utilization of OHS facilities are expected to enhance risk awareness and strengthen safety culture in the school environment